Ḫulāṣat al-ašʿār wa zubda al-afkār - Kāšānī, Mīr Taqī-ad-Dīn,Mīr Afḍalī, ʿAlī (Markaz-i Pizūhisī-i Mīrāt-i Maktūb, 2017)
Persian poetry - Iran - Yazd. ; Persian poetry - Iran - Kirman ; Poets, Persian - Iran - Yazd - Biography ; Poets, Persian - Iran - Kirmān - Biography
Keywords: Biografie; Poets; Persian; Persian poetry